Nghiên cứu hoàn thiện hệ thống thông tin thống kê xây dựng - Vũ, Văn Tuấn (2011)
Tác giả: Vũ Văn Tuấn, CN; Phạm Thị Hồng Trang; CN; Phạm Đình Thuý, ThS; Dương Trí Thắng, ThS; Mai Bá Thiện, CN -- Từ khóa: Thống kê xây dựng